2017
DOI: 10.1021/acsami.7b03705
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Tungsten-Doped SnO2 and Graphene Nanocomposites for High-Performance Anode Materials of Lithium-Ion Batteries

Abstract: The composite of tungsten-doped SnO and reduced graphene oxide was synthesized through a simple one-pot hydrothermal method. According to the structural characterization of the composite, tungsten ions were doped in the unit cells of tin dioxide rather than simply attaching to the surface. Tungsten-doped SnO was in situ grown on the surface of graphene sheet to form a three-dimensional conductive network that enhanced the electron transportation and lithium-ion diffusion effectively. The issues of SnO agglomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 58 publications
0
24
0
1
Order By: Relevance
“…Density-functional theory (DFT) calculations and electrochemical measurements reveal that W with a smaller electronegativity (1.5 vs. 1.9 of Co) and stable hexavalent state is a good dopant in CoP, [19] giving rise to more thermodynamically neutral ΔG H* as well as large water adsorption energy and enhanced electrochemical active surface area (ECSA) of WÀ CoP/ CC compared to the CoP/CC. The nanoneedle array provides abundant active sites and facilitates ions transport to benefit HER and OER.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Density-functional theory (DFT) calculations and electrochemical measurements reveal that W with a smaller electronegativity (1.5 vs. 1.9 of Co) and stable hexavalent state is a good dopant in CoP, [19] giving rise to more thermodynamically neutral ΔG H* as well as large water adsorption energy and enhanced electrochemical active surface area (ECSA) of WÀ CoP/ CC compared to the CoP/CC. The nanoneedle array provides abundant active sites and facilitates ions transport to benefit HER and OER.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the conductive and flexible carbon cloth (CC) offers 3D support to integrate the WÀ CoP catalysts thus resulting in fast electron transport and low interfacial resistance because of obviating the need for a polymeric binder. Density-functional theory (DFT) calculations and electrochemical measurements reveal that W with a smaller electronegativity (1.5 vs. 1.9 of Co) and stable hexavalent state is a good dopant in CoP, [19] giving rise to more thermodynamically neutral ΔG H* as well as large water adsorption energy and enhanced electrochemical active surface area (ECSA) of WÀ CoP/ CC compared to the CoP/CC. Consequently, the WÀ CoP/CC catalyst delivers excellent HER performance such as low overpotentials of 32 and 77 mV at a current density of 10 mA cm À 2 in 0.5 M H 2 SO 4 and 1 M KOH and small Tafel slope of 57 and 65 mV dec À 1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…One is to reduce the size of SnO 2 to nanoscale, and the other is to composite the SnO 2 with carbon materials. Although the nanostructure‐engineering strategy can enhance the life and capacities of batteries to a certain extent, the cycle number usually maintains at about 50 cycles, which is far below the expected performance . It was found that hybridization of nanoscale SnO 2 and carbonaceous materials could effectively solve the issues of large volume change and poor conductivity because the nanoscale SnO 2 can not only decrease the absolute volume variation but also the pathway of lithium‐ion diffusion and electron transfer, and at the same time, the conductive and flexible carbonaceous materials can not only improve the conductivity of whole electrode, but also buffer the volume variation of SnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have attempted to improve the lithiation rate of tin oxide‐based electrodes by increasing the electrical conductivity of SnO 2 via doping . SnO 2 ‐based anodes were doped with Sb, In, Zn, Co, Fe, Mo, Ti, W, and F; however, no improvement in the rate capability was observed. In‐ and W‐ doped SnO 2 /graphene composites reported by Liu et al and Wang et al reach only 200 and 300 mAh g −1 at a current densities of 7.8 and 7 A g −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%